Phosphorus Nutrition and Growth of Cotton Plants Inoculated With Growth-Promoting Bacteria Under Low Phosphate Availability - Romero-Perdomo, Felipe; Beltrán, Isidro; Mendoza-Labrador, Jonathan; Estrada-Bonilla, German; Bonilla, Ruth (Frontiers in Sustainable Food Systems, 2021)
The low availability of phosphorus (P) in the soil drastically limits the world productivity of crops such as cotton. In order to contribute sustainably to the solution of this problem, the current study aimed to evaluate the capacity of phosphate-solubilising bacteria to improve plant growth and its relationship with physiological parameters, as well as the shoot P content in cotton plants in a soil with low P availability amended with rock phosphate. The results showed that, of the six plant growth-promoting bacteria strains evaluated under greenhouse conditions, the Rhizobium strain B02 significantly promoted growth, shoot P content and photosynthetic rate. This strain improved the transpiration rate and the relative content of chlorophyll but without significant differences. Remarkably, Rhizobium sp. B02 had a more significant effect on plant growth compared to the P nutrition. Furthermore, the effect of its inoculation was more pronounced on the roots’ growth compared to the shoot. Finally, application of Rhizobium strain B02 showed the capacity to optimise the use of low-solubility fertiliser as the rock phosphate. These findings could be associated with the metabolic activities of plant growth promotion exhibited by phosphate-solubilising strains, such as phosphate solubilisation, production of indole compounds and siderophores synthesis. In conclusion, this research provides evidence of the biotechnological potential of the Rhizobium genus as phosphate-solubilising bacteria with multiple plant growth-promoting activities capable of improving the plant growth and phosphate nutrition of non-leguminous crops such as cotton in soil with low P availability amended with rock phosphate.